THE INFLUENCE OF CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO, OPERATIONAL COSTS OF OPERATIONAL REVENUE AND CREDIT DISTRIBUTION ON RETURN ON ASSET WITH NET INTEREST MARGIN AS AN INTERVENING VARIABLE IN CONVENTIONAL RURAL BANKS - Gialin Prihatna Putri br Sitepu; Nisrul Irawati; Fahmi Natigor Nasution (CV. Radja Publika, 2023)
This study aims to determine the effect of Capital Adequacy Ratio, Non-Performing Loans, Loan to Deposit Ratio, Operational Costs, Operating Income and Credit Disbursement on Return on Assets with Net Interest Margin as an Intervening Variable at Conventional Rural Banks in Medan City for the 2017-2021 period. In this study using secondary data collection in the form of financial reports that have been collected and published relating to the object of research. The data analysis method used to solve the problems in this research is descriptive statistical method, classic assumption test, panel data regression analysis method and expanded with sobel test analysis to test mediating (intervening) variables. The results showed that the Capital Adequacy Ratio had a positive and significant effect on Net Interest Margin at Conventional Rural Banks in Medan City, Non-Performing Loans had no significant effect on Net Interest Margin at Conventional Rural Banks in Medan City, Loan to Deposit Ratio had a positive effect and significant to Net Interest Margin at Conventional Rural Banks in Medan City, Operating Costs Operating Income has a negative and significant effect on Net Interest Margin at Conventional Rural Banks in Medan City. Credit Distribution has a positive and significant effect on Net Interest Margin at Conventional Rural Banks in Medan City.